Soybean Yield and Yield Components Depending on Sowing Rate and Sowing Date - Ana Pospišil; Milan Pospišil (Poljoprivreda)
A research on the influence of a sowing date on the soybean yield and the yield of its components was carried out at the Experimental Site of the Faculty of Agriculture of the University of Zagreb during 2019 and 2020. The study involved two soybean varieties, the AFZG Ana (maturity group 0) and Gabriela (maturity group 00-0), sown on the two sowing dates (i.e., an optimal and a late one) and three sowing rates: 40, 65, and 90 germinating seeds m-2. The sowing time did not have a significant effect on the soybean seeds’ yield and the yield of their components. In both research years, the Gabriela variety achieved a higher seed yield when compared to the AFZG Ana variety, which is a result of a higher number of nodes on the main stem, number of fertile nodes on the main stem, number of pods, number of seeds, and the seed weight per plant. The Gabriela variety achieved a significantly higher harvest index in both years. The seed yield increased with an increasing sowing density up to 65 seeds m-2. However, the differences were statistically significant only in 2019. The values of the yield components decreased with an increasing sowing density.